National Values and the Ways of Reading Them. Dialect Text at the Etnolinguist’s Workshop - Rutkovska, Kristina (Vilnius University Open Series, 2020)
The study aims to present certain methodological approaches used in the research of dialect narratives. In the introductory part of the article, the author discusses the links between the related sciences, analysing oral text: traditional dialectology, oral history and ethnolinguistics. The concept of cultureme as the unit describing realia, deeply entrenched in a certain type of culture, composing a certain identity of an ethnic group, is also introduced. The notion of a cultureme is very close to the notions of a keyword, described by Anna Wierzbicka, and a stereotype or concept, described by the ethnolinguistic school of Lublin. The difference, however, is that that the description of concepts is aimed at reflecting the folk or nationwide worldview and human view, while culturemes are used to identify a specific community, show the specificity of a certain region and its values. The example of the description of one cultureme (the manor) is used to provide the complicated structure of dialect narrative, its stylistic values, types of a narrator, and subjective way of perceiving and assessing the reality.
Keywords: oral history; ethnolinguistics; dialectology; folkloristics; dialect narrative